(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article discusses about updating of the Ukrainian lexis, in particular word- formation of feminine nouns in the system and structure of Ukrainian language that signalizes persistent tendency to regularity, and also about the willingness of society to record a new norm, overcoming asymmetric attitude toward men and women